2014
DOI: 10.1371/journal.pone.0109000
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Asthmatic Response after Ammonium Persulfate-Induced Occupational Asthma in Mice

Abstract: IntroductionSince persulfate salts are an important cause of occupational asthma (OA), we aimed to study the persistence of respiratory symptoms after a single exposure to ammonium persulfate (AP) in AP-sensitized mice.Material and MethodsBALB/c mice received dermal applications of AP or dimethylsulfoxide (DMSO) on days 1 and 8. On day 15, they received a single nasal instillation of AP or saline. Airway hyperresponsiveness (AHR) was assessed using methacholine provocation, while pulmonary inflammation was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
2
8
0
1
Order By: Relevance
“…This is compatible with a Th2 immunological response, despite the unexpected increases in levels of total serum IgG2a (characteristic of a Th1 stimulation in mice) from day 60. These results are consistent with other studies carried out by our group with the same animal model and other mouse models of asthma using LMW agents [ 9 , 11 , 20 23 ], which suggested a mixed Th2-Th1-type immune response in sensitized mice. It has also been proposed that an increase in IgG levels may have a protective effect in this animal model [ 24 ], as the percentage of neutrophils decreased at the same time point that IgG started to increase.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is compatible with a Th2 immunological response, despite the unexpected increases in levels of total serum IgG2a (characteristic of a Th1 stimulation in mice) from day 60. These results are consistent with other studies carried out by our group with the same animal model and other mouse models of asthma using LMW agents [ 9 , 11 , 20 23 ], which suggested a mixed Th2-Th1-type immune response in sensitized mice. It has also been proposed that an increase in IgG levels may have a protective effect in this animal model [ 24 ], as the percentage of neutrophils decreased at the same time point that IgG started to increase.…”
Section: Discussionsupporting
confidence: 93%
“…A semi-quantitative scoring system was used to grade the severity and extent of inflammation, as well as bronchiolar epithelium hyperplasia on H&E stained sections. The thickness of the infiltrate in the interalveolar septa and hyperplasia was graded as follows: 0 (normal) = absence of inflammatory cells; 1 (mild) = 1–2 layers of inflammatory cells; 2 (moderate) = 3–5 layers; 3 (severe) = more than 5 layers [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to studies with patients, experimental murine research on chemical‐induced asthma due to persulfate salts showed increased levels of total serum IgE . In these experimental studies, AHR, neutrophilic airway inflammation, increases in Th, Tc, and B‐lymphocytes, a mixed Th1/Th2 immune response derived from cytokine profiles in local draining lymph nodes and BAL fluid, and serum IgG1/IgG2a levels were reported after AP sensitization and challenge . Moreover, we were able to show that lymphocytes from sensitized mice could be directly triggered to proliferate by in vitro restimulation with the sensitizing agent.…”
Section: Discussionmentioning
confidence: 60%
“…AP, ammonium persulfate; BAL, bronchoalveolar lavage; CI, confidence intervals; IL, interleukin; NT, no treatment; T, treatment increases in Th, Tc, and B-lymphocytes, a mixed Th1/Th2 immune response derived from cytokine profiles in local draining lymph nodes and BAL fluid, and serum IgG1/IgG2a levels were reported after AP sensitization and challenge. 12,25 Moreover, we were able to show that lymphocytes from sensitized mice could be directly triggered to proliferate by in vitro restimulation with the sensitizing agent. These results suggest that OA due to persulfate salts may be caused by a complex interaction of an innate and a mixed Th1/Th2 adaptive immune response.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation